PENGARUH KINERJA MANAJER INVESTASI DAN KEBIJAKAN ALOKASI ASET TERHADAP KINERJA REKSA DANA SAHAM DI INDONESIA - Paramitha, A. A. Sagung Putra Pradnya; Purnawati, Ni Ketut (E-Jurnal Manajemen; Vol 6 No 8 (2017), 2017)
Mutual funds investment is indirect investment that apply the principles of portfolios diversification exist in the market. Applying the principles of portfolios diversification in the mutual funds can reduce loss-risk and in the long term can optimizing return that received by investor. Mutual funds are managed by professional hand, that makes limitation of direct investment can be solved. This research aims to know the effect Investment Manager Performance factor and Asset Allocation Policy factor partially to Equity Mutual Funds Performance in Indonesia. The number of the research samples are 40 equity mutual funds, that using census method in 3 years observation period. Research data analysis technique used multiple-linear regression. Research result states that Asset Allocation Policy partially have the positive and significant effect to Equity Mutual Funds Performance  in Indonesia. Investment Manager Performance have the negative and significant effect to Equity Mutual Funds Performance  in Indonesia.